Perbuatan Hukum Kurator Dalam Melakukan Penjualan Tanah Dan Rumah Atas Dasar PPJB Dan Menjadi Objek Pailit (Studi Putusan Mahkamah Agung No 436/Pdt.Sus-Pailit/2019) - Sagala, Liwarny; Sunarmi, Sunarmi; Siregar, Mahmul; Tony, Tony (Journal of Law & Policy Review, 2023)
In 2009 PT. Sarwo Indah sold one of the housing units in Merapi Regency with Lie Anita (hereinafter referred to as LA). In the process of settling the bankruptcy assets of PT. Sarwo Indah experienced legal problems which later became the focus of this research. As in the Determination of the Supervisory Judge in case Number: 02/Pailit/2011/PN. Commerce. Smg, dated 13 June 2014, one of the contents was the determination of the Curator appointed by PT. Sarwo Indah (in bankruptcy) on behalf of Nasrullah Nawawi. The type of research in this research is normative juridical. This type of research was used because the researcher wanted to examine something related to the curator's legal actions in selling land and houses on the basis of PPJB and becoming the object of bankruptcy. As long as the house certificate that is the object of the PPJB agreement is still in the name of the bankruptcy debtor, the house becomes a bankruptcy debtor. This is based on Article 21 of the K-PKPU Law which explains that bankruptcy covers all of the debtor's assets at the time the decision to declare bankruptcy is pronounced. Application of the Law of the Panel of Judges in Supreme Court Decision No. 436 K/Pdt.Sus-Pailit/2019 is appropriate considering the juridical aspect, namely referring to the applicable law, namely assessing the relationship between the function of the curator and the settlement of the bankruptcy estate's assets so that there is no obligation for the Curator to continue the agreement between the Buyer and Seller (in bankruptcy)